MEMORI KOLEKTIF KONFLIK DI ACEH DALAM NOVEL KAWI MATIN DI NEGERI ANJING KARYA ARAFAT NUR - Indra Dwi Wahyu; Sukirno Sukirno (Universitas Batanghari, 2025)
This research aims to analyze the collective memory of the conflict in Aceh and the formation of collective memory in the novel Kawi Matin di Negeri Anjing by Arafat Nur. This research uses Maurice Halbwachs' collective memory theory approach. This study employs a descriptive qualitative research method, which aims to address the research focus by providing detailed descriptions of the data. The research results show a collective memory of the conflict events in Aceh in the novel. The novel shapes collective memory through the portrayal of characters, the impact of the social environment, and the reconstruction of history. The findings show that literary works, especially novels, function as a medium that can reflect and preserve collective memory. Novels not only describe an event but also serve as a tool to build a group's identity and collective memory.